Reproduction of female identity in Indonesian novel Lelaki Harimau and its German translation Tigermann - Finalia, Cicu; Malik, M. Zulfi Abdul; Cleveresty, Tri Bigrit (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to explore the reproduction of female identity in the novel Lelaki Harimau by Eka Kurniawan and its German translation Tigermann. This study focuses on the representation of the identity of the female characters in both versions of the text, differences in attitude, judgment, and affect towards female characters in both versions of the text, and influence of the cultural norms of the target language in the reproduction of female identity in translation. This study employs the qualitative method with the approach of content analysis of both versions of the text. Data is obtained from portions of the texts that describe female characters. The results show that there are significant differences in the representation of female identity between the source text and the target text, caused by different lexical and grammatical choices. The German cultural norms influence the reproduction of female identity. The translator adjusted the gender characteristics and roles to fit the context of the target culture. This finding underlines the importance of gender sensitivity in the translation of literary texts and shows how translation is not only a process of transferring meaning, but it is also a medium that can reproduce gender identity, particularly female identity.